Spasmolytic, antimicrobial and cytotoxic activities of 5-phenylpentyl isothiocyanate, a new glucosinolate autolysis product from horseradish (Armoracia rusticana P. Gaertn., B. Mey. & Scherb., Brassicaceae). (1st October 2017) - Dekić, Milan S.; Radulović, Niko S.; Stojanović, Nikola M.; Randjelović, Pavle J.; Stojanović-Radić, Zorica Z.; Najman, Stevo; Stojanović, Sanja
Highlights: A new natural product 5-phenylpentyl isothiocyanate (PhPeITC) was found in horseradish. The first direct proof of the existence of a 5-phenylpentyl glucosinolate in nature. PhPeITC and four related isothiocyanates were synthesised and extensively tested. PhPeITC possesses spasmolytic activity 100 times more potent than papaverine. Horseradish constituents showed significant cytotoxicity and antimicrobial activity. Abstract: Detailed analyses of horseradish autolysates led to the identification of a new natural product, 5-phenylpentyl isothiocyanate (PhPeITC). The structural assignment was corroborated by synthesis, and the identity unequivocally established by spectral means. The occurrence of PhPeITC is the first direct proof of the existence of a 5-phenylpentyl glucosinolate in the aerial parts of this species as one of the possible "mustard oil" precursors. To verify its possible contribution to the horseradish functional food status, horseradish above- and underground autolysates, together with five ω-phenylalkyl isothiocyanates were tested for their spasmolytic, cytotoxic and antimicrobial activities. Specifically, the cytotoxic effect on Caco-2, HeLa (cancer) and MDCK (non-cancer) cell lines was established. Additionally, the five tested ITCs exerted significant spasmolytic activity (on rat distal colon), with PhPeITC being almost 100 times more potent than papaverine. A non-selective antimicrobial activity of all ITCs was revealed in the case of 6 bacterial and 2 fungal strains.